Watching Me Watching You: How Observational Learning Affects Self-disclosure on Social Network Sites?. Issue 1 (31st January 2018) - Ashuri, Tamar; Dvir-Gvisman, Shira; Halperin, Ruth
Abstract: Many explanations have been proposed regarding people's willingness to disclose information on social network sites (SNSs). Focussing on the reciprocal nature of such sites, this study explores the significant role observational learning (OL) plays in determining users' willingness to self-disclose information on Facebook. It demonstrates how the ability to view other users' actions—and the rewards and setbacks they encounter—impinge on their risk assessment and resulting disclosure behavior. Using an online survey of 742 Facebook users and an experiment conducted with 264 such participants, we demonstrated that users learn from others regarding self-disclosure behavior and resulting gains/losses. We showed that the observation mechanism contributes to reward envy, that leads to a high level of self-disclosure behavior. By contrast, observation of risks has only a marginal effect on such undertakings.